Goosebumps presents attack of the mutant - Metz, Melinda; Angel, Dan.; Brown, Billy; Stine, R. L. (New York : Scholastic, 1997)
Skipper Matthews sees a building in Riverview Falls that looks exactly like the secret headquarters of the Masked Mutant and wonders if the comic book villain is living in his hometown.
"A Parachute Press book"--T.p. verso.
3.5.
3.5
5-8
Keywords: Cartoons and comics -- Fiction; Horror stories; Horror fiction; Superhero comic books, strips, etc. -- Fiction